Sự tác động của phần mềm kế toán đám mây tới hiệu quả kinh doanh của doanh nghiệp nhỏ và vừa tại Việt Nam: Vai trò trung gian sự hài lòng của lãnh đạo cấp cao - Phạm Ngọc, Toàn; Đào Nhật, Minh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study is conducted to evaluate the mediating role of senior leader’s satisfaction in the relationship between cloud accounting software and business performance of small and medium enterprises (SMEs) in Vietnam. Based on DeLone & McLean (2016) information systems success model and Resource-based view of the firm, the authors propose that cloud accounting software has direct and indirect impacts (through senior leader’s satisfaction) on improving their business performance in SMEs in Vietnam. By employing a regression test with a sample of 132 SMEs based in Ho Chi Minh City, Binh Duong, and Dong Nai in Vietnam, the result indicates a satisfaction of senior leaders plays the mediating role in a relationship between cloud accounting software and business performance of SMEs in Vietnam. Therefore, cloud accounting software providers should pay attention to this factor when deploying cloud accounting software in SMEs to help SMEs achieving the highest business performance when they adopt cloud accounting software.